Preliminary findings of puma (Puma concolor) diet and livestock depredation in the Brazilian Caatinga - Borling, Jonatan (SLU/Dept. of Ecology, 2019)
The puma (Puma concolor) has the largest distribution of any mammal in the Americas, but has disappeared from large areas of its former range. Half of the puma’s current distribution lies within Brazil where it is listed as Vulnerable. One major threat to the puma is human-induced mortality due to depredation on livestock. Searching clusters of positions from GPS-collared carnivores is a useful method to investigate kill-rate on wild prey as well as livestock depredation. The goal of this study was to investigate parameters that could make cluster searches of puma more effective in the Caatinga biome in Brazil, and to preliminarily assess the proportion of livestock among prey. A female puma was fitted with a satellite GPS-collar in a mountainous area in Bahia, Brazil. 40 clusters from 17 consecutive puma days were visited. Eight prey items were found in these clusters. Five were domestic animals and three were wild prey. Domestic animals predated on were sheep (Ovis aries) and goat (Capra aegagrus) while wild prey were rock cavy (Kerodon rupestris), nine-banded armadillo (Dasypus novemcinctus) and six-banded armadillo (Euphractus sexcinctus). Domestic animals accounted for 93 % of body mass in carcasses found during the study period. The puma stayed for longer periods at larger prey. The amount of time it spent at a cluster was the only near-significant variable indicating that a cluster contained a kill site. Using a GPS position interval of one position every third hour would have led to all clusters with kill sites being found. Streamlining the method of cluster searches could make it useful for both puma and jaguar (Panthera onca) in Caatinga in the future. The study indicates that pumas kill livestock in Caatinga and that further studies are necessary in order to find suitable interventions to reduce livestock depredation.